2011
DOI: 10.1007/s00402-011-1342-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there an increased stem migration or compromised osteointegration of the Mayo™ short-stemmed prosthesis following cerclage wiring of an intrasurgical periprosthetic fracture?

Abstract: After wiring of an intrasurgical fracture, no disadvantage could be proven for Mayo prosthesis regarding stem migration and varus-valgus alignment. Furthermore, due to the absence of differences in the occurrence of radiolucent lines and the same results in the DEXA scan, an unimpaired osseointegration is assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This indicates that the stem size for SHA can as accurately be templated as the stem size for THA. This finding is relevant, as it had been discussed that SHA may cause a higher rate of femoral neck fractures during insertion [21]. However, a biomechanical study could demonstrate that the fracture risk with a proper implant size is equal for SHA and THA [22].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This indicates that the stem size for SHA can as accurately be templated as the stem size for THA. This finding is relevant, as it had been discussed that SHA may cause a higher rate of femoral neck fractures during insertion [21]. However, a biomechanical study could demonstrate that the fracture risk with a proper implant size is equal for SHA and THA [22].…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it can be speculated that some of the reported intra-operative fractures might be related to the use of an oversized SHA implant. This is underscored by a study of Zeh et al [21] who reported a high rate of femoral neck fractures during the learning curve for implantation of the Mayo stem. As the present study demonstrates that the stem size for SHA can exactly be determined in about 50 % of the cases and within one size margin in 89 %, this shows that a pre-operative templating is a useful tool to predict the proper implant size and thereby might be able to reduce intraoperative complications.…”
Section: Discussionmentioning
confidence: 98%
“…The radiological measurement of stem migration and angulation was not performed using an established method like EBRA [ 38 ]. However, the method used in this study has been validated and successfully performed in other similar investigations [ 15 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, patients were treated without weight bearing for 3 or 6 weeks, and after this 20 kg partial weight bearing before transition to full weight bearing. Another recent study showed that patients treated similarly to ours after intraoperative fracture using a mayo short stem prosthesis, had no disadvantages referring stem migration or alignment [23]. …”
Section: Discussionmentioning
confidence: 88%